Is failed predictive control a risk factor for focal dystonia?. Issue 12 (27th October 2016) - Stein, Peter; Saltzman, Elliot; Holt, Kenneth; Sternad, Dagmar
ABSTRACT: Introduction: Task‐specific focal dystonia (TSFD) is a disorder marked by degraded coordination in complex and exacting psychomotor tasks, such as musical performance. Its development is associated with prolonged and intensive practice of these tasks, but the etiology of TSFD is still unknown. The prevailing hypothesis was informed by findings in primates following repetitive simple grasping actions. This model implies, however, that complex manual tasks that yield more intricate and subtly varying sensorimotor patterns, as found in musical performance and handwriting, should be unlikely to lead to focal dystonia. Hypothesis: We propose an alternative, "predictive‐control" etiological hypothesis: When an overtaxed performer exhibits poorly controlled variability and errors in motor execution of a well‐learned, high‐precision task, predictive control processes deteriorate. This includes, in particular, those related to the formation or updating of a forward dynamic model that maps motor commands to predicted end‐effector state, e.g. position and velocity of a key‐pressing digit. Conclusion: Based on a critical literature review we argue that this results in the characteristic signs of focal dystonia, such as freezing, halting and inappropriate co‐contraction specific to the task. Directions for future research are briefly discussed. © 2016 International Parkinson and Movement Disorder Society.